Case Report: Challenges in the Diagnosis of a Case of Mal de Meleda and a Therapeutic Attempt of Ixekizumab and Adalimumab - Dai, Yuwei; Zheng, Xiaodong; Zhang, Qi; Hu, Xia; Wang, Peiguang; Yang, Sen (Frontiers in Medicine, 2022)
Background: Mal de Meleda (MDM, OMIM 248300) is an autosomal recessive disease characterized by symmetrical and progressive palmoplantar hyperkeratosis soon after birth. Mutations in SLURP1 gene could lead to MDM. Clinically, MDM is easily misdiagnosed as other types of keratoderma due to phenotypic variation and overlap. Objective and Methods: A patient with suspected MDM was confirmed by the combination of next-generation sequencing and Exomiser, and the patient was attempted with the treatment of Ixekizumab and Adalimumab. Results: A homozygous mutation c.256G>A (p.Gly86Arg) in the SLURP1 gene was identified in the patient. The inflammatory erythemas on his hands, feet and buttocks were mildly relieved after the treatment of high dose of Ixekizumab. Conclusions: Our findings helps to enhance the understanding of MDM. Ixekizumab may be a potential strategy to treat MDM.